2015
DOI: 10.2147/ijn.s85369
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate-loaded lipid-core nanocapsules are highly effective in the control of inflammation in synovial cells and a chronic arthritis model

Abstract: Background Rheumatoid arthritis (RA) is the most common autoimmune disease in the word, affecting 1% of the population. Long-term prognosis in RA was greatly improved following the introduction of highly effective medications such as methotrexate (MTX). Despite the importance of this drug in RA, 8%–16% of patients must discontinue the treatment because of adverse effects. Last decade, we developed a promising new nanocarrier as a drug-delivery system, lipid-core nanocapsules. Object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Autoimmune disorders (ADs) are categorized as chronic diseases derived from an imbalance between stimulatory and regulatory mechanisms of the immune system, strongly affected by the genetic predisposition and environmental condition. 14 The trigger of immune pathways and systemic inflammatory responses in AD may result in the damage of healthy tissues by over-reacted immune cells. Many of the proposed immunoregulatory approaches against ADs are developed based on the blockage of the interaction between antigen-presenting cells and T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Autoimmune disorders (ADs) are categorized as chronic diseases derived from an imbalance between stimulatory and regulatory mechanisms of the immune system, strongly affected by the genetic predisposition and environmental condition. 14 The trigger of immune pathways and systemic inflammatory responses in AD may result in the damage of healthy tissues by over-reacted immune cells. Many of the proposed immunoregulatory approaches against ADs are developed based on the blockage of the interaction between antigen-presenting cells and T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there may be some rationale behind repeated IA injections of MTX and indeed the 2018 study in our analysis showed a response [ 12 ]. These pharmacodynamics have generated an interest in developing conjugated compounds to provide longer retention of IA MTX [ 22 ]. For reference, the half-life of IA triamcinolone acetonide is between 3.2 and 6.4 days [ 23 ].…”
Section: Discussionmentioning
confidence: 99%